x = 2 , y = 3
(x + y ) + (x -4 ) - (5 -y) =
-(2x + y) - (3-x ) + (2y - 5 ) =



Odpowiedź :

Odpowiedź:

Proszę bardzo! ;)

[tex]x=2\\y=3\\\\a)\\(x+y)+(x-4)-(5-y)\\\\(2+3)+(2-4)-(5-3)=5-2-2=5\\\\b)\\-(2x+y)-(3-x)+(2y-5)\\\\-(2*2+3)-(3-2)+(2*3-5)=-(4+3)-1+(6-5)=-7-1+1=-7[/tex]

Szczegółowe wyjaśnienie:

Dane :

x = 2 i y = 3

Przykład I :

( x + y ) + ( x - 4 ) - ( 5 - y )

Podstawiamy :

( 2 + 3 ) + ( 2 - 4 ) - ( 5 - 3 ) = 5 - 2 - 2 = 5

Przykład II :

- ( 2x + y ) - ( 3 - x ) + ( 2y - 5 )

Podstawiamy :

- ( 2 · 2 + 3 ) - ( 3 - 2 ) + ( 2 · 3 - 5 ) = - ( 4 + 3 ) - 1 + ( + - 5 ) = - 7 - 1 + 1 = -7